High-Throughput Sequencing of the Expressed Torafugu (Takifugu rubripes) Antibody Sequences Distinguishes IgM and IgT Repertoires and Reveals Evidence of Convergent Evolution - Fu, Xi; Sun, Jianqiang; Tan, Engkong; Shimizu, Kentaro; Reza, Md Shaheed; Watabe, Shugo; Asakawa, Shuichi (Frontiers in Immunology, 2018)
B-cell antigen receptor (BCR) or antibody diversity arises from somatic recombination of immunoglobulin (Ig) gene segments and is concentrated within the Ig heavy (H) chain complementarity-determining region 3 (CDR-H3). We performed high-throughput sequencing of the expressed antibody heavy-chain repertoire from adult torafugu. We found that torafugu use between 70 and 82% of all possible V (variable), D (diversity), and J (joining) gene segment combinations and that they share a similar frequency distribution of these VDJ combinations. The CDR-H3 sequence repertoire observed in individuals is biased with the preferential use of a small number of VDJ, dominated by sequences containing inserted nucleotides. We uncovered the common CDR-H3 amino-acid (aa) sequences shared by individuals. Common CDR-H3 sequences feature highly convergent nucleic-acid recombination compared with private ones. Finally, we observed differences in repertoires between IgM and IgT, including the unequal usage frequencies of V gene segment and the biased number of nucleotide insertion/deletion at VDJ junction regions that leads to distinct distributions of CDR-H3 lengths.